Determining how andBeyond, a travel operator, make use of corporate social investment to strengthen brand equity in an African context. - Geyser, Dominique (The IIE, 2019)
When considering the concept of Corporate Social Investment (CSI) it is clear that the concept is not new. Numerous studies focusing on CSI have been conducted worldwide. Multiple theories as well as perspectives haven been developed around the concept of CSI. By implementing CSI initiatives, organisations have an opportunity to give back to the communicate as well as reflect a level of commitment to stakeholders. Consumers can be seen as one of the key stakeholder groups to any organisation and therefore the organisation should aim to meet the needs of this stakeholder group. This research has been driven by the need to understand the impact that CSI initiatives, undertaken by andBeyond has on the brand equity of the organisation. Literature regarding various topics relating to CSI, such as the benefits of CSI, consumer perceptions of CSI as well as consumer buying decisions were studied to gain a well-rounded understanding of the research objectives. The research included the collection of primary data through the use of a questionnaire. The questionnaire was distributed to consumers in order to gain an understanding of their views on the topic of the research. The study uncovered that consumers are interested in purchasing products and supporting andBeyond as they invest in CSI initiatives. The study shows that consumers are willing to continuously support andBeyond as long as the brand continues to meet high quality standards expected by guests.
Keywords: Brand; Corporate Social Investment; CSI; Brand equity; Consumer behaviour; Brand loyalty